The Development of Supplementary Teaching Material for Ibnu Hadjar’s Biography to Improve Collagers’ Critical Thinking Skills of History Education - Febri Irwandi; Joko Sayono; R Reza Hudiyanto (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: The purpose of this research is to improve capability of critical thingking of the student which relates to historical local figure of South Borneo. The realization of this research is research and develpoment (R&D). The explanation of Ibnu Hadjar's figure was realized in the form of Ibnu Hadjar's biography teaching material supplement products for students of history education offering B class of 2019 as an experimental class and Offering A as a control class at Lambung Mangkurat University who were taking Local History courses. The stages in this study use the 4D model that is indicated by four components, namely identification, design, development, and dissemination. The results of product validation and assessment include learning media expert validators with a percentage of up to 77% and are categorized as feasible to be implemented. The assessment of the material experts obtained a percentage of 91% with the category very feasible to be implemented. Obtaining language validation reached a percentage of 82% and included in the category eligible to be implemented. The student's assessment of teaching material supplement products reaches a percentage of 93% with a very good category. Assessment of lecturers supporting Local History courses obtained a percentage of 85% and can be categorized as interesting. As for the results of the effectiveness of the process of implementing the supplementary product of Ibnu Hadjar's biography teaching material to improve the critical thinking skills of students in the experimental class gained 82% percentage. This is very different from the results of students' critical thinking skills in the control class that were not given and implemented biography teaching material supplement products Ibnu Hadjar. The percentage gained in the control class only reached 56%.